Detection of Heat-labile Toxin and Evaluation of Antibiotic Resistance in Enterotoxigenic Escherichia Coli Isolated from Samples of Diarrhea in Children below 5 Years Old in Sari - Esmaeil Fattahi; Fatemeh Modanlou; Jafar Amani; Askari Ahmadpour (Majallah-i Dānishgāh-i ’Ulūm-i Pizishkī-i Īlām, 2018)
Introduction: Enterotoxigenic Escherichia coli (ETEC) is the most important agent which causes acute bacterial diarrhea throughout the world. ETEC binds to the intestinal mucosa and produce heat-labile enterotoxin (LT) and heat-stable toxin (ST), causinh disease in humans, especially in children. The present study was done for detection of heat-labile toxin and evaluation of antibiotic resistance in ETEC.   Materials & Methods: In this cross-sectional study, 90 stool samples for the isolation of Escherichia coli in children below 5 years-old were collected. At first, strains of E. coli, using biochemical tests, were isolated and the prevalence of ETEC strains and presence of gene LT toxin was, using PCR technique, investigated. Then, antibiotic sensitivity was studied by disk diffusion method.   Findings: Out of the 50 Escherichia coli isolates, 4 strains (8%) were containing LT toxin gene. All the strains ETEC containing LT toxin were quite resistant to antibiotics cotrimoxazole, cefixime, gentamicin (100%). Also, these strains proved to be sensitive to ceftriaxone, imipenem (100%), trimethoprim- sulfamethoxazole, ciprofloxacin, nalidixic acid, nitrofurantoin, tetracycline, amikacin (50%), ampicillin (25%), cefalotin (25%).   Discussion & Conclusions: The results showed that ETEC strain in the area of the outbreak is widespread. Therefore, application of rapid diagnostic techniques and precise molecular PCR and antibiotic resistance pattern can reduce diarrheal infections and help health promotion to prevent child deaths.